1988
DOI: 10.1079/bjn19880102
|View full text |Cite
|
Sign up to set email alerts
|

The effect of date of cut and barley substitution on gain and on the efficiency of utilization of grass silage by growing cattle

Abstract: 1. The effect of harvesting date of perennial ryegrass (Lolium perenne) on the nutritive value of the resultant silage and the effect of substitution of late-cut silage with barley was examined in growing cattle. The diets comprised early-cut (H) and late-cut (L) silage offered alone or with 280 (LCI) or 560 (LC2) g rolled barley/kg total dry matter (DM) substituted for late-cut silage.2. Both silages were prepared with the addition of formic acid (850 g/l; 2.4 litres/t fresh weight) to a partially wilted crop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
1

Year Published

1990
1990
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 13 publications
2
15
1
Order By: Relevance
“…Our results are consistent with those of Beever et al (1988), who concluded that reduced dietary fiber concentration is a very important factor increasing partial energetic efficiency as concentrate supplementation is used. Van Soest (1965) found that legumes had a smaller fraction of NDF than grasses.…”
Section: Energy and Carbon In Protein And Fat Ofsupporting
confidence: 93%
“…Our results are consistent with those of Beever et al (1988), who concluded that reduced dietary fiber concentration is a very important factor increasing partial energetic efficiency as concentrate supplementation is used. Van Soest (1965) found that legumes had a smaller fraction of NDF than grasses.…”
Section: Energy and Carbon In Protein And Fat Ofsupporting
confidence: 93%
“…For instance, if OMD were overestimated by 40 g/kg in comparison with the value reported by Kuoppala et al (2010), who determined digestibility by the total feces collection method in cows fed similar diets (comparable silage iNDF), then urinary energy excretion would be on average 7.7% lower. However the difference in urinary energy excretion between early and late cut silage was greater in this study than reported for lactating cows by Gordon et al (1995), who observed 77.4% greater energy output in urine with highly digestible silage, and in growing cattle by Beever et al (1988), who recorded 18.2% greater energy output in urine with highly digestible silage.…”
Section: Methane Emissions and Energy And N Utilizationcontrasting
confidence: 84%
“…A well-known methane mitigation strategy is to increase proportions of concentrate in the diet of dairy cows, especially above 35 to 40% of the diet (Sauvant and Giger-Reverdin, 2009), although exceptions occur where methane emissions have been increased (Beever et al, 1988). In the current study, methane production, regardless of the expression, was lowered in response to the HC diet (Table 5) with largest declines for Holstein cows.…”
Section: Effects Of Forage-to-concentate Ratiomentioning
confidence: 99%